Tenderness as an attribute of the romantic culture of love: specificity and features of manifestation - V. E. Turenko, (Ukrainian Cultural Studies, 2019)
Based on classical and modern philosophical works, the article conceptualizes the idea of tenderness as one of the key attributes of the dis- course of a romantic culture of love. The author notes that the idea of a close relationship of love and tenderness dates back to antiquity, namely the Platonic "Symposium". By analyzing in detail a fragment of this dialogue [Symp. 195d-e], the statement is substantiated that, manifesting itself as an attribute of love, tenderness has a powerful epistemological potential, which is expressed in the possibility of knowing the Other more deeply. Distinguishing between the verbal and non-verbal aspects of the manifestation of tenderness in a romantic culture of love, their general and distinctive features are highlighted. If the verbal aspect is not just words, epithets or metaphors, but acts as elements of power, then non-verbal manifestations of tenderness are defined as a kind of "words", "speech" to the Other. Revealing in detail the phenomenology of tenderness, it is proved that it has interior and exterior vectors, therefore there is a need not only to give tenderness, but also to accept from the person we love.Conclusions of the article. Being an attribute of a romantic culture of love, tenderness is the basis of its versatility in human destinies. Tenderness as one of the components of love, helps two loving people to know each other even more, especially regarding the vulnerability of participants in the discourse of love. Tenderness in the context of the discourse of the romantic culture of love is manifested in two aspects – verbal (gentle and affectionate words, epithets, metaphors) and non-verbal (kisses, hugs, touches). These two aspects of tenderness, being specific in manifestation, do not essentially contradict each other, but, on the contrary, complement each other, thus making a complete and true discourse of love. From a phenomenological point of view, tenderness, like love, is two-vector: it goes from I to You (Other) and from You (Other) to I. So, tenderness always involves reciprocity.
Keywords: tenderness, romantic culture of love, power, touch, speech, skin, vulnerability